THE EFFECT OF BOD GENDER AND LEVERAGE TOWARDS FIRM PERFORMANCE - Elfina Astrella Sambuaga; Leonardo Laksamana; Kevin Soetemto; Adrian Karundeng (UNKLAB Business School, 2022)
This research aims to investigate the effect leverage has towards firm performance when moderated by board of director’s gender. Net profit margin is used as the firm performance measure, both DAR and DER measures are used as leverage measure, and the as for BOD gender, dummy and proportion approach will be used. The research uses 69 out of 100 companies listed on Kompas100 on the year 2018 using purposive sampling method and the data is collected via Market Intelligence platform and inputted it to statistic software SPSS. The output shows that leverage has a negative impact towards firm performance and BOD gender weakens their negative relationship. This means that too much borrowing isn’t always necessarily good for a firm and females on the BOD can neutralize this effect. Keywords: BOD, firm performance, gender, leverage